Queer Compositions in a U.S. Secondary Classroom: Genre, Citationality, and Linguistic Racism. Issue 1 (12th March 2021) - Schey, Ryan
Abstract: In recent decades, there has been an increase in literacy education research attending to curriculum inclusive of sexual and gender diversity in secondary classrooms. Although valuable, most of this research has focused on the ideational and representational qualities of curriculum and thus has overlooked the significance of composition and genre. Seeking to add this scholarship, I focused on youth choosing to write about queer topics for compositional assignments in a secondary humanities course that combined English language arts and social studies (U.S. studies). Drawing from a broader literacy ethnography conducted at a high school in a Midwestern U.S. city, I argue that youth in the humanities course drew on curricular ideas and genres in their literacy performances in ways that resisted and reified oppressive values. Genres that encouraged extended dialogue resulted in interrogations of cisheteronormativity that were sustained and intersectional. However, youth's use of genres cited and reproduced racist and cisheteronormative Eurocentric, anti‐Black, and assimilationist ideologies. Hence, there is a need for approaches to queer‐inclusive curricula that explore intersections of queerness and race and attend to aspects of literacy and language practices beyond ideational and representational content.